Ethical Dilemma in Diabetes Wound Care: A Literature Review - Harsah Bahtiar Zainudin; Tantut Susanto (Babali Nursing Research)
Background: One of the main complications of diabetes is diabetic foot ulcer (DFU), which often requires intensive care and involves collaboration between various disciplines. In managing diabetic foot ulcers, several ethical dilemmas arise regarding autonomy, beneficence, non-maleficence, and justice. This review of the literature aims to examine ethical dilemmas in the care of diabetic wounds.